2010
DOI: 10.5694/j.1326-5377.2010.tb03482.x
|View full text |Cite
|
Sign up to set email alerts
|

Waiting lists and elective surgery: ordering the queue

Abstract: In the Australian public health system, access to elective surgery is rationed through the use of waiting lists in which patients are assigned to broad urgency categories. Surgeons are principally responsible for referring patients to waiting lists, deciding on the appropriate urgency category, and selecting patients from the waiting list to receive surgery. There are few agreed‐upon criteria to help surgeons make these decisions, leading to striking differences between institutions in proportions of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 14 publications
1
57
0
8
Order By: Relevance
“…Faced with ever-increasing cost constraints as well as demands for services, hospitals have experienced accelerating pressures to step up the pace [6, 13]. For example, time-based targets, such as the rule in Emergency Departments in the United Kingdom and Australia that people need to be seen within four hours [14, 15] and throughput pressures exemplified by elective surgery wait lists [16, 17] are pushing staff to fit more and more tasks into a set amount of time. Work is expanding in other ways too, such as with the introduction of burdensome documentation, rules and regulations [18].…”
Section: Introductionmentioning
confidence: 99%
“…Faced with ever-increasing cost constraints as well as demands for services, hospitals have experienced accelerating pressures to step up the pace [6, 13]. For example, time-based targets, such as the rule in Emergency Departments in the United Kingdom and Australia that people need to be seen within four hours [14, 15] and throughput pressures exemplified by elective surgery wait lists [16, 17] are pushing staff to fit more and more tasks into a set amount of time. Work is expanding in other ways too, such as with the introduction of burdensome documentation, rules and regulations [18].…”
Section: Introductionmentioning
confidence: 99%
“…Noseworthy et al. (2002), Gravelle and Siciliani (2008) and Curtis et al. (2010) have suggested that a more systematic and consistent system of urgency assignment may bring an outcome that promotes greater equity.…”
Section: Discussionmentioning
confidence: 99%
“…Waiting lists further provide a buffer between the demand for services and the capacity of the system to provide these services. They are consistently newsworthy as they are portrayed as one of the major issues experienced in government/tax‐funded health systems 12 . Waiting times for dental care are considered to be one of the major reasons for patient dissatisfaction 13–16 .…”
Section: Overview Of National Partnership Agreements For Dentistrymentioning
confidence: 99%
“…They are consistently newsworthy as they are portrayed as one of the major issues experienced in government/tax-funded health systems. 12 Waiting times for dental care are considered to be one of the major reasons for patient dissatisfaction. [13][14][15][16] It has been reported that those who waited less than 3 months experienced less inconvenience than those that waited for more than 3 months.…”
mentioning
confidence: 99%